STRATEGI SALATIGA MENUJU UNIVERSAL HEALTH CARE (UHC) MELALUI JAMINAN KESEHATAN NASIONAL - Putri Hergianasari; Suryo Sakti Hadiwijoyo (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Prof Dr Hazairin, SH, 2021)
Health is one of the basic rights possessed by everyone which is approved in various laws and constitutions. Therefore, health is a human right. The United Nations Development Program (UNDP) reported the level of health of the Indonesian people in 2008 was below the standards of countries in Asia. Improving Health Insurance for Indonesian needs to be Improved. This paper is intended to analyze the National Health Insurance, known as Social Security Administrator in the City of Salatiga, which is one of the downstream of Universal Health Coverage in realizing the United Nations program to provide health services to the public in accordance with the 1948 UN Declaration Article 25 paragraph 1. The method used in this research is to find Qualitative by using triangulation, namely direct observation in the field, interviews with relevant parties, and supporting documents. The results of this study analyze as part of the global development agenda as well as guarantee for human security. The implementation of the National Health Insurance in Salatiga City in 2018-2019 has increased mainly due to individual coverage and budget, although it has not met the UHC 95% target in 2019. This shows that Universal Health Coverage (UHC) is a form of protection of human rights as well as strategic steps to ensure human security, especially in the health sector.